Impact of small molecules on β-catenin and E-cadherin expression in HPV16-positive and -negative squamous cell carcinomas - Kramer, Benedikt; Hock, Clemens; Lammert, Anne; Walter, Beatrice; Birk, Richard; Hörmann, Karl; Aderhold, Marc Christoph (Anticancer research, 2017)
Background: The validation of potential molecular targets in head and neck squamous cell carcinoma (SCC) is mandatory. β-Catenin and E-cadherin are crucial for cancer progression through epithelial-mesenchymal transition. We analyzed the effect of the tyrosine kinase inhibitors nilotinib, dasatinib, erlotinib and gefitinib on β-catenin and E-cadherin expression in SCC with respect to human papillomavirus (HPV) status. Materials and Methods: Expression of β-catenin and E-cadherin in cell lines UMSCC 11A, UMSCC 14C and CERV196 under the influence of tyrosine kinase inhibitors were analyzed by enzyme-linked immunosorbent assay. Results: All agents reduced β-catenin and E-cadherin expression of HPV16-negative cells. Increased E-cadherin expression was observed after treatment with gefitinib and dasatinib in HPV16-positive cells. Conclusion: All substances, nilotinib, dasatinib, erlotinib and gefitinib have a significant impact on β-catenin and E-cadherin expression in both HPV16-positive and HPV16-negative cells in vitro. Alterations of β-catenin and E-cadherin could provide novel insights for future targeted therapies of head and neck SCC.